Приближенный расчет энерговыделения и электрической эрозии электродов в высоковольтном сильноточном воздушном коммутаторе атмосферного давления - Баранов, М.И.; Рудаков, С.В (Електротехніка і електромеханіка, 2017)
Приведены результаты применения нового инженерного подхода к расчету тепловой энергии, выделяющейся в плазменном канале искрового разряда и на массивных металлических электродах высоковольтного сильноточного воздушного коммутатора (ВСВК) атмосферного давления, используемого в составе высоковольтной электрофизической
установки (ВЭФУ) с мощным емкостным накопителем энергии (ЕНЭ). Полученные соотношения для определения
указанной энергии позволяют выполнять расчетную оценку баланса электрической энергии в разрядной цепи ВЭФУ с
ЕНЭ с учетом ее тепловых потерь в ВСВК. Показано, что на основе разработанного подхода может быть выполнен
расчет электрической эрозии основных металлических электродов ВСВК. Получены новые расчетные выражения для
нахождения глубины одиночного кратера разрушения на металлических электродах ВСВК и массы металла, выбрасываемой искрой из электродов исследуемого коммутатора за один разряд ЕНЭ установки. Приведені результати застосування нового інженерного підходу до розрахунку теплової енергії, що виділяється в плазмовому каналі іскрового розряду і на масивних металевих електродах високовольтного сильнострумного повітряного
комутатора (ВСПК) атмосферного тиску, використовуваного у складі високовольтної електрофізичної установки
(ВЕФУ) із потужним ємнісним накопичувачем енергії (ЄНЕ). Отримані співвідношення для визначення вказаної енергії дозволяють виконувати розрахункову оцінку балансу електричної енергії в розрядному колі ВЕФУ із ЄНЕ з урахування її теплових втрат у ВСПК. Показано, що на основі розробленого підходу може бути виконаний розрахунок електричної ерозії основних металевих електродів ВСПК. Отримані нові розрахункові вирази для знаходження глибини
одиночного кратера руйнування на металевих електродах ВСПК і маси металу, що викидається іскрою з електродів
досліджуваного комутатора за один розряд ЄНЕ установки. Purpose. To obtain new calculation correlations, determining
approximate energy dissipation and electric erosion of massive
basic metallic electrodes in the high-voltage high-current air
switchboard (HVCAS) of atmospheric pressure, in-use in the bit
chain of the high-voltage electrophysics setting (HVES) with the
powerful capacity store of energy (CSE). Methodology. Electrophysics bases of technique of high-voltage and large impulsive
currents (LIC), scientific and technical bases of development
and planning of high-voltage heavy-current impulsive electrodevices, including HVES and powerful CSE, and also methods
of measuring in their bit chains of LIC of the microsecond temporal range. Results. On the basis of new engineering approach
the results of calculation estimation of excretions energy and
electric erosion of massive basic metallic electrodes are resulted
in probed HVCAS. New correlations are obtained for the approximate calculation of thermal energy, selected in an impulsive air spark and on the workings surfaces of anode and cathode of HVCAS. It is entered and a new electrophysics concept,
touching equivalent active resistance of impulsive air spark, is
mathematically certain. New formulas are obtained for the approximate calculation of most depth of single round crater of
destruction on the workings surfaces of basic metallic electrodes
of HVCAS, and also mass of metal, thrown out magnetic pressure from this crater of destruction on the electrodes of switch
for one electric discharge through them powerful CSE HVES. It
is shown that the radius of the indicated single crater of destruction is approximately equal to the maximal radius of plasma
channel of a spark discharge between a cathode and anode of
HVCAS. The executed high-current experiments in the bit chain
of HVES with powerful CSE validated row of the got and in-use
calculation correlations for the estimation of energy dissipation
and electric erosion of metallic electrodes in examined HVCAS.
Originality. New engineering approach is developed for the
approximate calculation and estimation of energy dissipation
and electric erosion of basic metallic electrodes in HVCAS. A
formula is firstly got for approximate calculation unchanging in
the process of swaying or aperiodic discharge of CSE HVES on
the electric loading of active resistance of impulsive air spark
between the electrodes of probed HVCAS. Practical value.
Drawing on the got results in a high-voltage impulsive technique provides operative implementation of calculation of balance of electric energy in the high-current circuit of HVES with
powerful CSE and point electric load, and also prognostication
of the technical state of workings surfaces of massive basic metallic electrodes of HVCAS.